Methodology of B2B Customer Segmentation in the Utilities on the Czech Market Tool for Customer Classification into Segments - Filová, Andrea (2011)
Loyalty, improvement, better understanding of customers -- all these notions attract the interest and striving for improvement of many managers. The segmentation has become an indispensable part of path from a company to customers. Dividing market into distinctive groups allows a company to target customers in a better way. The energy industry in the Czech Republic is an example where the segmentation methodology is not working clearly, so entire organisations become disoriented as an effect of not clear B2B customer division. As there are not so many segmentation tools that would be made exclusively for an energy company, I decided to study this field and design a new one. In the first part, I will look into the energy industry specificities and functioning of the electricity market in order to understand the specifics of this industry on the Czech market. By looking into segmentation methods, particularly in the area of B2B, the important assumptions of the correct and effective segmentation will be discovered. In the second part, I applied the knowledge from the theoretical framework where the basic knowledge about the B2B market and the segmentation in this area were introduced. Moreover, the most appropriate variables of segmentation were grouped in the logical way. This knowledge will be used as a base for the creation of new segmentation methodology and application of the knowledge gained from the extensive research conducted abroad. All in all, the ultimate goal of my work is to create the new advanced segmentation methodology tool and to propose how the most suitable solutions can be designed.